Minimization of delays of road users on regulated crosswalks - Грицай, Сергій Васильович; Трушевський, Вячеслав Едуардович; Никифоровський, Данило Олексійович (Eastern-European Journal of Enterprise Technologies, 2014)
Several methods, used for determining the parameters of traffic light control cycles at crosswalks considered in the paper. It was found that they have disadvantages: do not take into account the delay time of pedestrians, do not allow to balance the duration of enable signals for transport and pedestrians. It was found that improved traffic light cycle structure at crosswalks is effective only at a high discipline of pedestrians, which depends on the justification of their delays by intense transport phases. In order to expand the scope of effective application of traffic lights at crosswalks, a method for determining the parameters of the control cycle at a crosswalk, based on the alignment and minimization of delay times for all road users, passing through the crosswalk is provided. This takes into account the values of all variables, influencing on the total hour duration of the delay of all road users. The implementation of this method will allow to enhance the capacity of crosswalks for both transport and pedestrians by reducing the groups of road users, gathering for the time of disable signals and improve traffic safety by reducing the number of violations by pedestrians.